EMG-Based Control of Active Ankle-Foot Prosthesis (Journal of Engineering, 2023)
Most below-knee prostheses are manufactured in Iraq without considering the fast progress in smart prostheses, which can offer movements in the desired directions according to the type of control system designed for this purpose. The proposed design appears to have the advantages of simplicity, affordability, better load distribution, suitability for subjects with transtibial amputation, and viability in countries with people having low socio-economic status. The designed prosthetics consisted of foot, ball, and socket joints, two stepper motors, a linkage system, and an EMG shield. All these materials were available in the local markets in Iraq. The experimental results showed that the maximum range of motion to move the designed prosthetic in the sagittal and frontal planes reached 70% of the healthy foot range of motion relative to the signals of the gastrocnemius muscle of a healthy leg person. The angles that represented the range of motion achieved in various directions at the ankle joint were Dorsiflexion Angle (35˚), Plantar Flexion Angle (25˚), Inversion Angle (20˚), and Eversion Angle (15˚).